sove equation -4+(-1)+2+.........+x=437
Answers
Answered by
3
common difference=3; first term=-4
so sum = (n/2){2a+(n-1)d}
=(n/2)(-8+3n-3)= (n/2)(3n-11)=437
3n^2- 11n -874=0
solve it for n then find Nth term
so sum = (n/2){2a+(n-1)d}
=(n/2)(-8+3n-3)= (n/2)(3n-11)=437
3n^2- 11n -874=0
solve it for n then find Nth term
Answered by
0
See this attachment
This is the best possible answer
Attachments:
![](https://hi-static.z-dn.net/files/da0/c64a660d90e5303e471e57b7b30d5530.jpg)
Similar questions
English,
9 months ago
Physics,
9 months ago
Computer Science,
1 year ago
Biology,
1 year ago
Math,
1 year ago